The Effects of Allogeneic Blood Transfusion in Hepatic Resection. Issue 2 (February 2021) - Inoue, Yoshihiro; Ishii, Masatsugu; Fujii, Kensuke; Kitada, Kazuya; Kuramoto, Toru; Takano, Yoshiaki; Matsuo, Kentaro; Tomioka, Atsushi; Yamaguchi, Toshifumi; Yokohama, Keisuke; Ohama, Hideko; Harada, Satoshi; et al.
Background: Hepatectomy has a high risk of perioperative bleeding due to the underlying disease. Here, we investigated the postoperative impact of allogeneic blood transfusion during hepatectomy. Methods: The surgical outcomes in 385 patients who underwent hepatic resection for hepatocellular carcinoma were retrospectively reviewed. The association of allogeneic blood transfusion with surgical outcomes and remnant liver regeneration data was analyzed. Results: Eighty-six patients (24.0%) received an allogeneic blood transfusion and 272 patients (76.0%) did not. After propensity score matching, the incidence rates of postoperative complication (Clavien-Dindo grade >IIIA), posthepatectomy liver failure, and massive ascites were significantly higher for the group that received a blood transfusion than for the group that did not receive blood transfusion ( P < .001, P = .001, and <.001, respectively). Postoperative measures of total bilirubin, albumin, platelet count, prothrombin time, aspartate aminotransferase, and alanine aminotransferase were significantly more favorable in patients without blood transfusion until day 7 after surgery. There were no correlations in the remnant liver regeneration at 7 days, and 1, 2, 5, and 12 months postoperatively between the 2 groups ( P = .585, .383, .507, .261, and .430, respectively). Regarding prognosis, there was no significant difference in overall and recurrence-free survival between the 2 groups ( P = .065 and .166, respectively). Conclusion: Allogeneic transfusion during hepatectomy strongly affected remnant liver function in the early postoperative period; however, this was not related to the remnant liver regeneration volume. Despite that the allogeneic transfusion resulted in poorer postoperative laboratory test results and increased postoperative complication and mortality rates, it had no effect on the long-term prognosis.